An Analysis of Reading Passages in Thai Language Textbooks “Wiwittaphasa” of Junior High School Level - Kongrat, Chedtharat (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research article were 1) to analyze passages in Thai language textbook, “Wiwittaphasa” of junior high school level in terms of forms, purposes and values of the passages; 2) to analyze the congruence of the passages in Thai Language textbooks, “Wiwittaphasa” of junior high school level based on Basic Education Core Curriculum 2008. The content analysis were 42 passages derived from 3 Thai Language textbooks, “Wiwittaphasa”, of junior high school level. The results of the analysis of passages in Thai Language textbooks, “Wiwittaphasa”, for the junior high school level were as follows: 1. The analysis of the passages in the textbooks shows that 1) The forms to present the passages are mostly in the prose form. 2) The purposes of the passages were to educate mostly in various disciplines. 3) The values found in the passages were mostly promoted the desirable characteristics. 2. The congruence between the reading passages and the Basic Education Core Curriculum 2008 shown that the contents in the passages are congruent with the curriculum. It played as an important role for learners to achieve the goals of the curriculum as follows: 1) For Knowledge, the contents were to educate the main points of various disciplines. 2) For Skills, the contents were to found the basis for learners to develop thinking skills, to think hierarchically in accordance with the difficulty of each level. 3) For Attributes, the contents created learning experience that allowed learners to apply the knowledge in their daily lives, and to be able to live happily with others in society as Thai citizens and global citizens. When considering the key competency of the learners according to the curriculum, it was found that the reading passages encouraged learners to develop important learning competencies such as communication capacity, thinking capacity, problem-solving capacity, capacity for applying life skills, capacity for technological application.